2019
DOI: 10.1016/j.vpoa.2019.100016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pour-on administration of eprinomectin on milk yield and somatic cell counts in dairy ewes naturally infected with gastrointestinal nematodes

Abstract: Highlights Eprinomectin pour-on was highly effective against sheep nematodes. Eprinomectin pour-on increased daily milk yield of dairy ewes. Somatic cell counts were reduced improving the udder health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Currently, eight avermectins are licensed as veterinary drugs and insecticides, namely abamectin, ivermectin, doramectin, emamectin benzoate, selamectin, moxidectin, milbemycin oxime and eprinomectim [9]. They have complex ring structures (Figure 1), with a 16-membered macrocyclic ring, containing a spiroketal group, a benzofuran ring and disaccharide functionality [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, eight avermectins are licensed as veterinary drugs and insecticides, namely abamectin, ivermectin, doramectin, emamectin benzoate, selamectin, moxidectin, milbemycin oxime and eprinomectim [9]. They have complex ring structures (Figure 1), with a 16-membered macrocyclic ring, containing a spiroketal group, a benzofuran ring and disaccharide functionality [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this group, eprinomectin (EPR) is a substance that stands out for not accumulating in the tissues, making the withdrawal period unnecessary for the consumption of meat and milk and, therefore, can be recommended for lactating cows [10]. Among avermectins, EPR is the only one licensed for the treatment of parasitic infections in lactating cows, due to the zero-day withdrawal period for milk [9,11]. EPR is a semi-synthetic lactone of the avermectin family, registered as a broad-spectrum endectocide, constituted by the mixture of two homologues, eprinomectin B1a (≥ 90%) and eprinomectin B1b (≤ 10%), which differ by a methylene group at position C25 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis quantified the mean loss in milk yield to 22 % in infected compared with uninfected dairy sheep ( Mavrot et al, 2015 ). Effective anthelmintic treatment of infected dairy ewes appears to lead to longer milking periods ( Suarez et al, 2009 ), improved lactation persistence ( Fthenakis et al, 2005 ) and lower somatic cell counts ( Arsenopoulos et al, 2019 ), whereas effects of GIN infections on milk components are not consistent across studies. While Sechi et al (2010) did not find effects of GIN infection on milk components, Cruz-Rojo et al (2012) reported lower total milk protein contents.…”
Section: Introductionmentioning
confidence: 99%